Heritage links: Luiz de Castro Faria and the preservation of archaeological monuments in Brazil - Lucieni de Menezes Simão (Boletim do Museu Paraense Emílio Goeldi. Ciências Humanas, 2009)
The article analyses anthropologist Luiz de Castro Farias’s (1913-2004) participation in the debate about the 1961 Archaeology Law (Nº. 3.924), which touches upon archaeological monuments in Brazil. The connections between Rodrigo Melo Franco de Andrade (1898-1969), the Director of Historical and Artistic Heritage National Service (SPHAN) with Castro Faria who took over as Director of Quinta da Boa Vista National Museum, in Rio de Janeiro, and was member of Heritage Advisory Council, have been discussed. The importance of Castro Farias’s role in the implementation of the Archaeology Law, mainly from his research on sambaquis, has been reevaluated during the examination of his personal files. The paper highlights his contribution to management of inventory projects, documentation and register of archaeological sites.